Coprodução de biodiesel e triacetina por interesterificação enzimática de óleo de babaçu com acetato de etila - Nascimento, Camila Santos do (2025)
The growing global demand for energy and the environmental impacts associated with the intensive use of fossil fuels have driven the search for more sustainable routes for biofuel production. In this context, biodiesel stands out as a renewable alternative, particularly in Brazil, where its blending with fossil diesel is mandatory and currently corresponds to 15% (v/v). The conventional production route, based on chemical transesterification, generates large amounts of low-value glycerol and requires additional purification steps. As an alternative, this study investigated the co-production of biodiesel and triacetin through the enzymatic interesterification of babassu oil with ethyl acetate, a more sustainable reagent and compatible with en-zymatic catalysis. The process was carried out using the commercial lipase Eversa® Transform 2.0, previously immobilized on a hydrophobic Purolite® C18 support to enhance biocatalyst stability and enable reuse. Initially, babassu oil was character-ized in terms of its physicochemical properties and fatty acid composition. Subse-quently, a Central Composite Rotational Design was applied to evaluate the effects of temperature and the oil-to-ethyl acetate molar ratio on the yield of fatty acid ethyl esters (FAEEs). The optimal conditions were validated in a mechanically stirred re-actor with conventional heating, and the effects of enzyme loading and ethyl acetate addition mode were investigated. Under the optimized conditions: 15% enzyme load-ing (w/w relative to the oil), gradual addition of ethyl acetate, a temperature of 38 °C, and 72 h of reaction, the system with conventional heating achieved yields of 53.83% FAEEs and 2.10% triacetin. The application of microwave-assisted heating enabled comparable yields in a significantly shorter reaction time, reaching 57.58% FAEEs and 3.53% triacetin in only 6 h. These results demonstrate the potential of the enzymatic interesterification of babassu oil with ethyl acetate as a more sustain-able alternative route for biodiesel production, combined with the generation of tri-acetin as a higher value-added coproduct, and highlight the advantages of micro-wave heating for process intensification.